Developing the Kid-Bright board for controlling lamps and fans as game-based learning for twelfth-grade students - Lakhonmoon, Thinakon; Rutanatarntong, Yaovared; Noisombut, Teerachati (Journal of Education and Learning (EduLearn), 2025)
This research aimed to develop and evaluate a gamified learning game using the Kid-Bright board to teach introductory coding skills for controlling lamps and fans to 12th-grade students. The study employed a mixed-methods approach, involving the design and development of the game based on gamification principles, followed by an evaluation by three computer science experts to assess its suitability and effectiveness. The game was then implemented with a sample of 27 randomly selected 12th-grade students from Nong Kungsri Wittayakarn School in Kalasin Province, Thailand. Pre- and post-tests were conducted to measure learning outcomes, and a student satisfaction survey was administered to gauge their experience. The findings revealed that the developed game met the 80/80 criterion for efficiency (80.25/84.81), demonstrating its effectiveness in enhancing students' learning progress. The game also received high suitability ratings from experts (X̅=4.24, S.D=0.43) and garnered substantial satisfaction from the students (X̅=4.78, S.D=0.42), underscoring its potential as an effective and engaging tool for teaching basic coding skills in a real-world context.